2011
DOI: 10.1177/0003319710394164
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy is Associated With Increased Serum Levels of Uric Acid in Type 2 Diabetes Mellitus

Abstract: We assessed serum uric acid (SUA) levels in patients with type 2 diabetes mellitus (T2DM) with or without peripheral neuropathy (diagnosed by the Neuropathy Disability score [NDS]). We enrolled 64 patients with T2DM with peripheral neuropathy (group A: 31 men, mean age 63.0 ± 2.8 years) and 66 age-, gender-, renal function- and T2DM duration-matched patients without neuropathy (group B: 32 men, mean age 62.4 ± 3.1 years). Serum uric acid was significantly higher in group A (P < .001). There was a significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 46 publications
(56 reference statements)
8
50
0
5
Order By: Relevance
“…Also, previous studies found that elevated levels of HbA1c, FPG, TG, and LDL-C, but declined levels of HDL-C have been implicated in the progression of DPN [19][20][21].…”
Section: Discussionmentioning
confidence: 90%
“…Also, previous studies found that elevated levels of HbA1c, FPG, TG, and LDL-C, but declined levels of HDL-C have been implicated in the progression of DPN [19][20][21].…”
Section: Discussionmentioning
confidence: 90%
“…Serum hs-CRP is independently associated with development of diabetic neuropathy and diabetic foot ulcers [37]. On the other hand, Herder et al [38] observed no associations between CRP and neuropathy in a population-based survey of older people with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum levels of omentin, an adipokine with anti-inflammatory, insulin-sensitizing, and cardioprotective properties, were reduced in T2D individuals with DSPN, independently of established risk factors of polyneuropathy [89]. In T2D, there is also evidence of increased serum uric acid in the presence of DSPN [93,94]. Future studies should clarify the temporal sequence and causality of these associations.…”
Section: Inflammationmentioning
confidence: 97%